BCT506: Mechanical Properties of Bio-Composites / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (2018)
This course will expose students cognitively and technically to bio-composites, specifically to their mechanical properties. Early in the course the students will engage briefly on the chemical and anatomical structures of woody plant-based material. In general, the course will discussed the basic loads experienced by bio-composites in service and their reactions to these loads. The loads discussed will be the compression, tension, shear, bending and torsion. The course will explain the different types of load models. The failure modes will also be described in relation to the materials, applied loads, and service environment. Students will be exposed to analytical solutions to some of the real world problems associated with the mechanical properties of bio-composites. Lecture sessions will employ a mixture of lectures and active learning (self and peer discussions). The outcomes shall be assessed through a variety of tools which include the paper examination, assignments and classroom engagements.